2014
DOI: 10.1002/oa.2382
|View full text |Cite
|
Sign up to set email alerts
|

Different Preparation Techniques - Similar Results? On the Quality of Thin-Ground Sections of Archaeological Bone

Abstract: Palaeohistology as a valuable diagnostic instrument is dependent on the production of high‐quality thin‐ground sections from dry bone. The objective of this study was to consider technical differences and assess the qualitative outcomes of five techniques for preparing thin‐ground sections from dry archaeological bone. Established techniques with long follow‐up times and excellently documented results were compared with simpler and cheaper time‐saving techniques. Evaluations were made of the quality of thin se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…Not only can this be used as a complementary method to the bone exterior shape and size data, but histological analyses can also be applied to fragmented human remains where the external anatomy is compromised (Crescimanno & Stout, 2012; Cuijpers, 2006; Cummaudo et al, 2019; Haas & Storå, 2015; Lemmers, Gonçalves, Cunha, Vassalo, & Appleby, 2020). On the basis of our data, future researchers may be able to estimate which anatomical region a mid‐shaft femoral fragment derives from.…”
Section: Resultsmentioning
confidence: 99%
“…Not only can this be used as a complementary method to the bone exterior shape and size data, but histological analyses can also be applied to fragmented human remains where the external anatomy is compromised (Crescimanno & Stout, 2012; Cuijpers, 2006; Cummaudo et al, 2019; Haas & Storå, 2015; Lemmers, Gonçalves, Cunha, Vassalo, & Appleby, 2020). On the basis of our data, future researchers may be able to estimate which anatomical region a mid‐shaft femoral fragment derives from.…”
Section: Resultsmentioning
confidence: 99%
“…These remains were donated to the school for research purposes and fall under the South African Human Tissues Act. Cadavers were used because Beauchesne and Saunders (2006) and Haas and Stora (2014) had very little success using Maat et al's (2001) manual grinding method to prepare very fragile bone samples. Beauchesne and Saunders (2006) also indicated that modern bone and archaeological bone of good preservation would be best suited for the manual method and defined good preservation as "bone that had not been greatly affected by taphonomic changes, thereby maintaining much of its original mineral and organic composition and thus its stiffness and strength" (Beauchesne and Saunders, 2006: 84).…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative comparisons between an automated and Maat et al's (2001) manual grinding technique were investigated by Beauchesne and Saunders (2006) where each technique was found directly comparable to one another using both modern bone and archaeological bone of good preservation. For very fragile bone samples, the automated technique produced higher quality sections compared to the manual grinding technique (Beauchesne and Saunders, 2006;Haas and Stora, 2014). Although modern bone and well preserved archaeological bone were found qualitatively equivalent for the two techniques, a quantitative analysis comparing an automated grinding technique to Maat et al's (2001) manual grinding technique has not been attempted.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…A relatively quick, easy and cheap method provides a solution for less equipped laboratories (Maat et al, 2001). With modifications, the method is also suitable for fragile or even cremated remains (Maat et al, 2001;De Boer et al, 2013a;Haas and Storå, 2015). The destructive sampling that is inevitably needed for histological analysis may be seen as a hard to overcome necessity.…”
Section: Challenges Related To the Analysis Of Ancient Tissue Samplesmentioning
confidence: 99%